Teaching literature and language through multimodal texts - Dominguez Romero, Elena; Bobkina, Jelena; Stefanova, Svetlana (IGI Global, 2019)
"This book applies multiple language teaching modalities for the teaching of language through literature in the context of primary, secondary and higher education. It offers insight on the impact of such practice on learners with the intention to inspire other teachers to reconsider their own teaching practices"...
Keywords: English language -- Study and teaching -- Foreign speakers -- Audio-visual aids; Second language acquisition -- Audio-visual aids